Quality of Engineering Education in Some of the Engineering Colleges within Pune University Area - Junnarkar, N. D. (Journal of Engineering Education Transformations, 2010)
Engineering is the profession in which knowledge of mathematical and natural sciences, gained by study, experience and practice is applied with judgement to develop ways to utilize economically the materials and forces of nature for the benefit of mankind. Engineers turn ideas into reality; they create useful products and systems through playing with imagination and possibilities, leading to new and meaningful connections and outcomes while interacting with ideas, people and environment.